Residential Segregation - Matthias Bernt; Anne Volkmann (Encyclopedia, 2023)
Residential segregation refers to the disproportionate distribution of population groups across a geographical area. Groups can be segregated on the basis of any characteristic (such as occupation, income, religion, age or ethnicity) and at any geographical scale. In most cases, segregation is, however, measured with regard to residential areas of a city. The extent of the unequal distribution of selected characteristics can be expressed by different statistical measures. Sociologists, economists and demographers have long studied how social groups tend to be differentiated in residential space and developed a broad range of explanations. As a consequence, segregation has been explained by a variety of theories, which are discussed in this paper. The topics examined by empirical research include temporal dynamics, geographical patterns, societal causes and effects on life chances. This entry focuses on major conceptual facts regarding residential segregation and only marginally discusses the methodological issues connected with its measurement.
Keywords: 300